Central Asian transport corridors issue in the scientific literature (International relations and international law Journal, 2019)
The article describes the main views of domestic and foreign experts on the development of transport corridors in Central Asia. The relevance of the problem is explained by the expansion of transport infrastructure in the Central Asian region within the framework of both national and international programs. The participation of Central Asian countries allows to solve a number of problems through the realization of the country’s transit potential. However, in the process of implementing infrastructure projects, regional states face risks that require a correlation of transport policies with the national interests of the countries. This explains the wide scientific interest in this issue. The expert community is increasingly focusing on issues of transport policy of states and international cooperation on transport projects. Despite the large number of works on various aspects of international and regional transport corridors, in the scientific literature there are no works of a complex nature, studying the transport corridors of Central Asia. This also applies to historiographic research.Key words: transport corridors, Central Asia, transit potential, expert community, national interests, risks.